O lugar da educação física na educação infantil - Martins, Rodrigo Lema Del Rio (2018)
The general objective of this thesis is to analyze the forms that have characterized the relationships between Physical Education and Infant Education, through the following dimensions: legal/pedagogical documents that guide the pedagogical practices of Child Education throughout the country; academic-scientific productions of Physical Education on Early Childhood Education; menus/bibliographies of the subjects that theme the Infant Education in the physical education training courses of the public universities of the country and teacher’s discourses of the teachers that work in the public networks of the Brazilian capitals. We hypothesize that the distances between these different dimensions make it difficult for Physical Education to find its place in Early Childhood Education, understanding that this place is expressed by the role that this area of knowledge occupies in this stage of Basic Education. The specific objectives are: a) to analyze the presence of Physical Education in Early Childhood Education based on the assumptions that underlie the National Curricular Guidelines for Early Childhood Education and the National Curricular Common Base; b) to discuss the relationship between Physical Education and Early Childhood Education, through academic and scientific productions of the area and about childhood, in interface with the documents (DCNEI, 2013, BNCC, 2016) that guide this first stage of Basic Education in Brazil; c) identify, through the menus/bibliographies of the subjects related to Early Childhood Education of the physical education training courses of the Brazilian public universities, the points of convergence and divergence that they establish with the presuppositions present in said documents; d) understand, through the discourses, how the teachers who work in the public education networks of the Brazilian capitals develop and base their pedagogical practices, converging or not with the findings in the other dimensions investigated. This thesis combines two different research methods: documentary-bibliographic research (LIMA, MIOTO, 2007) and descriptive-interpretive research (THOMAS; NELSON, 2002). The sources used were: 3 official documents, 117 scientific articles, 76 theses/dissertations, 25 academic papers and the menus and bibliographies of 30 subjects of 18 undergraduate courses in Physical Education. A total of 142 Physical Education teachers working in 10 Brazilian capitals participated in this study. In the process of analysis, the data of Chapters II, III and IV were interpreted with the help of the Iramuteq software, through the instruments of the cloud of words and similarities. In Chapter IV, we used the contributions of the Theory of Social Representations (MOSCOVICI, 2003), focusing on the Central Core of Representations (ABRIC, 2003; SÁ, 2002), to examine the answers that participants gave to our questionnaire. It is concluded that the place of Physical Education in Infant Education is in constant dispute, permeated by tensions (disciplinarization of Infant Education, fragmentation of knowledge, exclusivity/specificity of body/movement) and positions (curricular prescriptions for Early Childhood Education, physical education courses and by the academic community in scientific production). In this way, the subjects that integrate this field (BOURDIEU, 2004) coexist, act and react in function of the diverse contingencies expressed in the official documents, in the academic-scientific production, in the curricula of formation and in the teaching discourses.